А. Г. Кавтарадзе. Военные специалисты на службе Республики Советов - Буравченков, А. О.; Верстюк, В. Ф. (Український історичний журнал, 2025)
А. Г. Кавтарадзе. Военные специалисты на службе Республики Советов. — 1917—1920 гг. М.: Наука, 1988. — 278 с.